Breaking the Headscarf Ban in Secular Turkey: An Alternative Educational Establishment in Istanbul - Haliloğlu, Nagihan (Bloomsbury Academic, 2014)
This paper examines the programme at Akademistanbul, an alternative establishment of higher learning in Istanbul, and the particular niche it caters for in the Turkish educational system. Its students are all female, and they all wear the headscarf. As such, Akademistanbul is one of the institutions of higher learning that has been welcoming to hijabi women even in a period of headscarf ban in universities. Akademistanbul offers programmes in Islamic studies, Arabic and Psychology and its trajectory reveals the interesting shift in what routes girls who have been barred from going to secular universities may follow for higher learning. My paper will look at the curriculum of the academy and include interviews with the students and staff to see where they place it in the constellation of the alternative institutions of higher learning in Turkey, particularly in relation to theology faculties at ‘secular’ universities.
FSM Vakıf Üniversitesi, Medeniyetler İttifakı Enstitüsü
Keywords: Turkey; Secularism; Alternative education; Hijab ban; Psychology